Механизмы формирования современной французской произносительной нормы - Короткова, М.О. (Культура народов Причерноморья, 2014)
Статья посвящена изучению понятия французской произносительной нормы, проблеме ее определения и механизмам формирования. В ней определяется место нормы в языковой системе, а также рассматривается характер изменения нормы в процессе становления и развития языка. Стаття призначена вивченню поняття французькоī вимовної норми, проблемi її визначення та механiзмам формування. У нiй визначається мiсце норми у мовнiй системi, а також розглядається характер змiни норми у процесi становлення та змiни мови. The article is dedicated to the study of the notion of French orthoepic norm, the problem of its definition and mechanisms of its formation. The notion of the norm is rather ambiguous and its different aspects are usually highlighted by scientists when giving its definition. Generally they mark out three principal dimensions in the notion of the norm: the objective norm, the subjective norm and the axiological norm. In conditions of community development, continuous linguistic and social changes, interdependent and interacting, the norm is a fundamental regulator of speech activity. It is clear that normative speech is the obligatory sign of well-educated, cultured person and the culture of sounding speech is an important aspect of national culture such as the culture of written word, communication or social life in general. The orthoepic French norm has been evolved in the process of French language development. It is absolutely related to historical, social and culture processes. The norms are not invented by philologists, they reflect a certain stage of literary language development. In the article the role of the norm and its place in the language is defined and norm evolution in the process of language establishment and development is considered.